Anterior Knee Pain after Bone Patellar Tendon Bone Graft for Arthroscopic-Assisted Anterior Cruciate Ligament Reconstruction - Niazi, Javaid Iqbal; Amin, Muhammad Suhail; Swati, Muhammad Arsalan Azmat; Aslam, Zeeshan; Kakkar, Zainullah; Habib, Adeel (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the change in frequency and intensity of anterior knee pain after a bone patellar tendon bone graft for arthroscopic-assisted anterior cruciate ligament reconstruction after 06 months. Study Design: Longitudinal study. Place and Duration of Study: Department of Orthopedics Combined Military Hospital, Rawalpindi Pakistan, from Jul 2019 to Jun 2021. Methodology: We studied 100 patients who underwent Anterior Cruciate Ligament reconstruction and met our inclusion criteria. A Visual Analogue Scale pain score was used to assess anterior knee pain in this group. They were reevaluated at four weeks, eight weeks, and twenty-four weeks. Results: The data of 100 patients (mean age of 29.2±6.71 years) who underwent Anterior Cruciate Ligament reconstruction surgery and followed prescribed rehabilitation protocol was analysed. The VAS scores of all patients at 04 weeks, 08 weeks and 24 weeks were evaluated. The incidence of severe anterior knee pain was 3 patients (3%) at 04 weeks and 1 patient (1%) at 6 months. The frequency of patients in the moderate pain category was 13(13%), 06(06%) and 04(04%) at the 04, 08 and 24 weeks, respectively. At the four-week follow-up, 44 patients (44%) were pain-free, increasing to 70 patients (70%) at the six-month follow-up. Conclusion: At six months following Anterior Cruciate Ligament repair with bone patellar tendon bone graft, there was a significant reduction in the intensity of anterior knee discomfort in patients.